Development of a shear device for precise simple shear measurements of rubber mats. (20th January 2021) - Kanzenbach, Lars; Ihlemann, Jörn
Abstract: This contribution deals with the development of a new shear specimen, which allows precise simple shear measurements for large shear values. The main idea is that the shear load for the rubber mat is applied via steel pins. A form fit connection has the advantage that for the load application, no clamping force or high friction coefficient is required. In addition, the disadvantages resulting from vulcanisation or bonding, for example, shrinkage, are avoided. This offers the big advantage that homogeneous ageing tests can be performed, and also fibre‐reinforced materials can be tested. In order to show the potential of the new pin design, simulation results are compared to each other, and also a first experimental implementation is conducted. The new shear specimen can be used for phenomenological investigations of rubber properties, like Payne effect, Mullins effect, anisotropy, permanent set, softening, recovery, creep and relaxation behaviour.